Akibat Hukum terhadap Akta Pernyataan Keputusan Rapat yang Tidak Sesuai Antara Agenda Rapat dan Pelaksanaan Rapat Pembina Yayasan: (Studi Kasus Putusan Nomor: 389/Pdt.G/2019/Pn Bdg) - Anna Loist; Triono Eddy; Juli Moertino (Pusat Riset dan Inovasi Nasional, 2026)
This study aims to analyze the legal status of the Deed of Decision of the Foundation's Board of Trustees Meeting which was made not in accordance with the meeting agenda, identify legal problems arising from procedural defects, and examine the legal responsibility of notaries and foundation trustees as reflected in the Decision of the Bandung District Court Number 389/Pdt.G/2019/PN Bdg. The method used is normative juridical with a case approach and statute approach. Primary data was obtained from the court decision, while secondary data came from Law Number 28 of 2004 concerning Foundations, its implementing regulations, and related legal literature. The results of the study indicate that the deed of decision of the board of trustees meeting which was not in accordance with the meeting agenda in this case was declared invalid and not binding because it contained procedural defects and was contrary to the principle of justice. As a result, various legal problems arose, such as unlawful acts, flawed meeting decisions, notarial deeds that lost their force, and potential sanctions for notaries. Legal responsibility in this case rests with both the notary and the foundation's trustees, who can be held civilly liable for damages and immaterial losses.